2022
DOI: 10.1001/jamanetworkopen.2021.45319
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antihypertensives That Stimulate vs Inhibit Types 2 and 4 Angiotensin II Receptors With Cognitive Impairment

Abstract: Key Points Question Are antihypertensive medications that stimulate type 2 and 4 angiotensin II receptors, compared with those that do not stimulate these receptors, associated with a lower risk of incident cognitive impairment? Findings In a secondary analysis of the Systolic Blood Pressure Intervention Trial (SPRINT), this cohort study of 8685 patients found that prevalent use of medication regimens that contain exclusively angiotensin II receptor type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…10,11 ARBs, which selectively block the AT1Rs without inhibiting ACE and result in the relatively upregulated activities of AT2Rs and AT4Rs, and keep the pathway of Aβ degradation mediated by ACE intact, may offer superior protection than simultaneously lowering all the angiotensin receptors' activities with ACE inhibitors. Recent studies recognized that compared with angiotensin-inhibiting antihypertensives, angiotensin-stimulating antihypertensives conveyed a lower risk of incident cognitive impairment and dementia, 12,34 supporting the angiotensin hypothesis.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…10,11 ARBs, which selectively block the AT1Rs without inhibiting ACE and result in the relatively upregulated activities of AT2Rs and AT4Rs, and keep the pathway of Aβ degradation mediated by ACE intact, may offer superior protection than simultaneously lowering all the angiotensin receptors' activities with ACE inhibitors. Recent studies recognized that compared with angiotensin-inhibiting antihypertensives, angiotensin-stimulating antihypertensives conveyed a lower risk of incident cognitive impairment and dementia, 12,34 supporting the angiotensin hypothesis.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…Previous observational studies have reported that prevalent use of regimens containing antihypertensive medications that stimulate type 2 and 4 angiotensin II receptors, compared with those that do not, were associated with lower rates of incident mild cognitive impairment and dementia . However, those studies were limited by the inclusion of individuals with prevalent hypertension and relatively small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that, specifically, these angiotensin II (ATII)-stimulating antihypertensive users had a 45% lower dementia risk compared with users of other AHM types in the Prevention of Dementia by Intensive Vascular care (preDIVA) population [ 15 ]. This finding was recently replicated in the SPRINT-MIND trial population, wherein ATII-stimulating AHM users had a 24% lower dementia risk when compared with other AHM users [ 16 ]. Moreover, we previously observed that individuals who used ARBs and CCBs at baseline had an approximately 40% lower dementia risk compared with individuals using other AHM types over 6.7 years of follow-up [ 17 ].…”
Section: Introductionmentioning
confidence: 81%
“…Several hypotheses exist around the potential neuroprotective effects of CCBs and ARBs, ranging from their abilities to improve cerebral blood flow, reduce cerebral oxidative stress markers, and protect against neuronal death [32]. In addition, dihydropyridine CCBs and ARBs stimulate AT2 and AT4 receptors through the ATII pathway, which potentially protects against ischemia and preserve memory, respectively [15,16,[33][34][35][36]. An important potential challenge in studies with dementia as outcome is the competing risk of mortality before the development of dementia.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation